Modern slavery: a global perspective - Kara, Siddharth (Columbia University Press, 2017)
Acknowledgments -- Slavery and human trafficking: an overview -- Sex trafficking : the case of Nigeria -- Labor trafficking : slavery at your dining table -- Organ trafficking : sold for parts -- Technology and human trafficking : friend and foe -- Debt bondage : beyond South Asia -- Global supply chains : blood and the sea -- A framework to eradicate slavery -- Appendix A: Global slavery metrics -- Appendix B: Select slavery economics -- Appendix C: Sample research questionnaire -- Notes -- References -- Index